QUALITATIVE AND QUANITATIVE RESPONSE OF FORAGE MAIZE CULTIVARS TO SOWING METHODS UNDER SUBTROPICAL CONDITIONS - W. Ahmad; A.U. H. Ahmad; M. S. I. Zamir; M. Afzal. A. U. Mohsin; F. Khalid; S. M. W. Gillani (Journal of Animal and Plant Sciences, 2012)
Field experiment was conducted at Agronomic Research Area, University of Agriculture, Faisalabad, Pakistan to study the influence of different sowing methods on the growth, yield and quality of different cultivars of forage maize (Zea maysL.). The experiment was laid out in randomized complete block design (RCBD) with split arrangement having three replications. The net plot size was 3 m x 6 m. The experiment was comprised of three varieties viz. Neelum, Pakafgoi and Sargodha 2002 and three sowing methods viz. broadcast, 30 cm apart single row and 45 cm apart double row strip. The growth, yield and quality parameters differed significantly among the different cultivars and sowing methods. The results exhibited that the maximum plant height (202.47 cm), number of leaves plant-1 (13.5), plant population m-2 (44.16) at harvest, , leaf area plant-1 (3885 cm-2), fresh weight plant-1 (551.67 g), dry weight plant-1 (111.63 g), green forage yield (56.65 t ha-1), dry matter yield (10.90 t ha-1), crude protein ( 8.76%)and crude fibre (30.93%) showed that sowing method S2, 30 cm apart single row with variety V2 (Pakafgoi) provided favorable conditions for increasing the growth and yield of maize as compared to  other treatments under the environmental conditions of Faisalabad.
Keywords: Maize forage; varieties; sowing methods.